2007
DOI: 10.1108/07419050710836036
|View full text |Cite
|
Sign up to set email alerts
|

Internet Use by Research Scholars in University of Delhi, India

Abstract: PurposeThe paper seeks to examine the use of Internet among the research scholars of the Central Science Library (CSL), University of Delhi, India. The prime objective is to find out the current trends in information search through Internet by the research scholars and type of problems faced by them in their research work.Design/methodology/approachTools used for the study are questionnaire, observation and informal interview using stratified method. Content analysis is used to analyse open‐ended questions. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 11 publications
4
20
0
Order By: Relevance
“…The findings is congruent with earlier report of Madhusudhan (2007) and Kaur and Manhas (2008) which revealed that research scholars had preference for Google though the reports of Ehikhamenor (2003) and Oduwole (2004) had indicated Yahoo as the most used search engine among Nigerian academics. Nazim (2008) identified Google and Yahoo as the most widely used search engines for their wide coverage, regular updating and fastness in access.…”
Section: Major Findings and Discussionsupporting
confidence: 93%
“…The findings is congruent with earlier report of Madhusudhan (2007) and Kaur and Manhas (2008) which revealed that research scholars had preference for Google though the reports of Ehikhamenor (2003) and Oduwole (2004) had indicated Yahoo as the most used search engine among Nigerian academics. Nazim (2008) identified Google and Yahoo as the most widely used search engines for their wide coverage, regular updating and fastness in access.…”
Section: Major Findings and Discussionsupporting
confidence: 93%
“…For the academicians in the University of Delhi, India, the usefulness of the Internet is shown through the frequency of its use. Most of the respondents used the Internet more frequently, with 70 percent of them indicated using it daily, 16 per cent of them more than two or three times in a week, 12 per cent of them once a week and 2 per cent of them occasionally [2]. Internet presence helps to improve the educational process and address problems related to weak collaborative partnerships, declining educational standards, rising costs, increasing student numbers and to meet the general increased demand for higher education [3].…”
Section: B Internet Usage By Academicians World-widementioning
confidence: 99%
“…Madhusudhan [16] conducted a survey on Internet use by research scholars at Delhi University, which reveals that most respondents used search engines more than subject gateways or web directories to locate information. Asemi [13] findings revealed that Google search engines are mostly used by the respondents while searching for information on the Internet with 68%, followed by Yahoo, AltaVista, MSN and HotBot with 61%, 15%, 11% and 4% preference respectively.…”
Section: Search Engines Used By Researchers To Search and Locate Infomentioning
confidence: 99%